2015
DOI: 10.1097/aap.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Chronic Pain

Abstract: The combination of obesity and pain may worsen a patient's functional status and quality of life more than each condition in isolation. We systematically searched PubMed/MEDLINE and the Cochrane databases for all reports published on obesity and pain. The prevalence of combined obesity and pain was substantial. Good evidence shows that weight reduction can alleviate pain and diminish pain-related functional impairment. However, inadequate pain control can be a barrier to effective lifestyle modification and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 211 publications
(248 reference statements)
3
58
1
Order By: Relevance
“…In their review of the literature on pain and obesity, Narouze and Souzdalnitski [18] indicate that the relationship between obesity and chronic pain has been a focus of attention since the late 1990s, and that the evidence points to a strong association between these chronic conditions. The evidence provided in their review of high-quality studies demonstrates a relationship between obesity and pain in weight-bearing joints, but also between obesity and headache/migraine pain, upper extremity pain, chronic widespread pain and fibromyalgia, abdominal/pelvic pain and chronic neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their review of the literature on pain and obesity, Narouze and Souzdalnitski [18] indicate that the relationship between obesity and chronic pain has been a focus of attention since the late 1990s, and that the evidence points to a strong association between these chronic conditions. The evidence provided in their review of high-quality studies demonstrates a relationship between obesity and pain in weight-bearing joints, but also between obesity and headache/migraine pain, upper extremity pain, chronic widespread pain and fibromyalgia, abdominal/pelvic pain and chronic neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that multidisciplinary chronic pain management programs commonly include approaches to increase activity [19]. Additionally, it is not uncommon for weight gain to follow injury and pain in childhood [20], and some pain medications (e.g., pregabalin and gabapentin) are associated with weight gain [18]. Therefore, educating parents about the importance of weight, nutrition and physical activity is important, regardless of the weight status of the patient at the time of intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests an association between chronic pain and poor diet quality with higher intakes of energy-dense, nutrient poor foods [8,9]. There are a number of studies that explore the association between obesity and chronic pain, including a recent systematic review summarizing the evidence which supports the notion that there is a higher prevalence of chronic pain in people who are obese, compared to a normal weight population [10]. This review further emphasizes the importance of including weight reduction in chronic pain management [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies that explore the association between obesity and chronic pain, including a recent systematic review summarizing the evidence which supports the notion that there is a higher prevalence of chronic pain in people who are obese, compared to a normal weight population [10]. This review further emphasizes the importance of including weight reduction in chronic pain management [10]. Other studies have also reported a link between greater pain perception and a higher weight status, with individuals classified as obese twice as likely to experience pain [11,12].…”
Section: Introductionmentioning
confidence: 99%